Twisted properties of banach spaces - Castillo, Jesús M. F.; Gonzáles, Manuel; Plichko, Anatolij M.; Yost, David (MATHEMATICA SCANDINAVICA, 2001)
If P, Q are two linear topological properties, say that a Banach space X has the property P-by-Q (or is a P-by-Q space) if X has a subspace Y with property P such that the corresponding quotient X/Y has property Q. The choices P,Q {separable, reflexive} lead naturally to some new results and new proofs of old results concerning weakly compactly generated Banach spaces. For example, every extension of a subspace of L_1(0,1) by a WCG space is WCG. They also give a simple new example of a Banach space property which is not a 3-space property but whose dual is a 3-space property.